Somna - Cloonan, Becky (DSTLRY Media, Inc., 2024)
"BECKY CLOONAN and TULA LOTAY - both writing and drawing a graphic novel together for the FIRST TIME! Set amidst the terrifying backdrop of the witch hunts in a quiet 1600s English village, SOMNA follows one woman's descent into an erotic escape from the confines of her puritanical world. Ingrid is unhappily married to Roland, the town's bailiff and chief witch hunter, who is on a single-minded quest to purge the 'heretics' in their midst. After a prominent town leader is found murdered, accusations fly and no one is above reproach from Roland's deadly crusade. Ingrid has her suspicions about who the real murderer is, but even as she pursues the truth, she's pursued herself by a shadowy figure. Ingrid finds that she's drawn to the foreboding phantom in ways she can't resist- does this dark and tempting strangermay hold the key to the mystery...or will he damn Ingrid's soul to the blackest circle of Hell? From the masterful minds of Becky Cloonan (BY CHANCE OR PROVIDENCE, Wonder Woman) and Tula Lotay (BARNSTORMERS) comes an intoxicating blend of history, eroticism, and the supernatural in SOMNA-an evocative masterpiece that draws inspiration from cinematic folk-horror gems like Midsommar and The Witch- and will transport readers to a world where passion and spirits intertwine, enrapturing your senses and leave you craving more. For fans of The Witch and Midsommar." --